Surgery 101 Podcast: Episodes 61-70 - Jonathan White; Keith Rourke; Nishan Sharma; Jenni Marshall; Shannon Erichsen; Katrina Pederson; Simon Byrns (Association of American Medical Colleges, 2012)
Abstract This resource is a collection of podcasts that serve as brief introductions to or reviews of surgical topics for medical students. Each podcast is approximately 10-15 minutes long so that learners can quickly get a good idea of the basic concepts involved. Every episode is divided into chapters and concludes with several key points to summarize the topic. This particular collection of podcasts covers the surgery consult, presenting your case to a surgeon, learning in the surgical clinic, and several modules on urology. These podcasts have been very well received by local students and have been downloaded more than 25,000 times from iTunes. Please note that these podcasts are intended only as brief introductions for medical students as the authors could not delve into the more complex nuances of advanced surgery in a 10-minute podcast. All listeners are encouraged to supplement their learning by seeing patients, assisting at surgeries, and reading widely.